NILAI BUDAYA PADA KANAL YOUTUBE DONGENG KITA SEBAGAI IMPLIKASI BAHAN AJAR BAHASA INDONESIA DI SEKOLAH DASAR - Muharromah, Wulandari; Firman Syah, Ezik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem in this study is the decline in the application of cultural values of elementary school students. This study aims to analyze the cultural values of elementary school students on the Dongeng Kita YouTube channel and describe the implications of Indonesian language teaching materials on the Dongeng Kita YouTube channel in elementary schools. This type of research is qualitative with a content analysis method. This data was obtained through folklore videos on the Dongeng Kita YouTube channel and the results of the analysis of cultural values on the Dongeng Kita YouTube channel as implications of Indonesian language teaching materials in elementary schools. The data analysis of this study used the Milles and Huberman model. The results obtained from this study were that the cultural values contained on the Dongeng Kita YouTube channel include: 1) cultural values of human relations with God found two criteria, namely, piety and prayer, 2) human relations with nature found the use of natural resources to meet their daily needs, 3) human relations with society in the form of deliberation, 4) human relations with others include politeness, mutual assistance, compassion, and keeping promises and 5) human relations with themselves, namely self-confidence, patience, and hard work. The implications of the teaching materials used on the Dongeng Kita YouTube channel can be useful in the use of appropriate, enjoyable, efficient teaching materials, supporting the teaching and learning process in the classroom and helping to instill and develop students' character through the habits of the characters contained in the folk tales on the Dongeng Kita channel.